Efeito dos parâmetros de dispersão sobre a dinâmica espaço-temporal do pulgão Aphis gossypii Glover: uma abordagem computacional - Mendes, Cristian Tiago Erazo (2017)
With the purpose of getting a larger control of that plague, studies are accomplished for best to understand the characteristics of the population dynamics of this insect. A model computacional quite used in population dynamics with age structure is the model Penna. Some adaptations of this model for study of the population dynamics of different species are found in the literature. The objective of this work was to analyze the dynamics space-storm of the aphid A. gossypii in cotton plant culture, using the adaptations of the model Penna proposed by (AMARAL, 2014). More specifically, the behavior of the population dynamics by alterations in relative parameters to the dispersion of apterous and winged. In the obtained results it was observed small alterations in the population average and intrinsic growth rate due to alterations in the relative parameters to the dispersion. On the other hand, it was observed the influence of the migration of apterous on the time of infestation of the plants in the net. For all the dispersion parameter sets an aggregate distribution pattern, an anisotropic behavior of the spatial distribution, as well as the formation of a clustered percolation were observed in moments close to the occurrence of maximum variance and the inflection point of the population mean.